2019
DOI: 10.3389/fimmu.2019.00631
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aryl Hydrocarbon Receptor (AhR) in the Regulation of Immunity and Immunopathology During Trypanosoma cruzi Infection

Abstract: Resistance to Trypanosoma cruzi infection is dependent on a rapid induction of Th1-type and CD8+ T cell responses that should be promptly balanced to prevent immunopathology. T. cruzi -infected B6 mice are able to control parasite replication but show a limited expansion of Foxp3+regulatory T (Treg) cells that results in the accumulation of effector immune cells and the development of acute liver pathology. AhR is a ligand-activated transcription factor that promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 81 publications
2
24
0
Order By: Relevance
“…144 In the experimental model of Chagas disease, AHR activation expands the Treg compartment, increasing parasite replication. 145 In agreement with these findings, AHR-deficient mice show reduced T. cruzi parasitemia and a heightened immune response characterized by the production of proinflammatory Fig. 2 Role of AHR in infections targeting the CNS.…”
Section: Role Of Ahr In Infections Targeting the Cnssupporting
confidence: 59%
See 1 more Smart Citation
“…144 In the experimental model of Chagas disease, AHR activation expands the Treg compartment, increasing parasite replication. 145 In agreement with these findings, AHR-deficient mice show reduced T. cruzi parasitemia and a heightened immune response characterized by the production of proinflammatory Fig. 2 Role of AHR in infections targeting the CNS.…”
Section: Role Of Ahr In Infections Targeting the Cnssupporting
confidence: 59%
“…Notes: (NP) nanoparticles, (ROS) reactive oxygen species, (NO) nitric oxide cytokines, increased NO in serum, and downregulation of SOCS2. 145,146 Conversely, within the context of infection by Toxoplasma gondii, AHR deficiency results in higher mortality as a result of increased pro-inflammatory responses and decreased IL-10 production. 147 Taken together, these findings highlight the complex roles played by AHR in infection: AHR can limit immunopathology but can also be exploited by pathogens to evade the immune response.…”
Section: Role Of Ahr In Infections Targeting the Cnsmentioning
confidence: 99%
“…We and others have shown that during the early phase of T. cruzi infection, as in other parasitic diseases, the limitation of Treg cells allow the emergence of the protective T cell-dependent response (30,34,51,52). However, reduction in Treg frequency can result in a massive accumulation of effector immune cells and immunopathology, as is observed in T. cruzi-infected B6 mice (34,53).…”
Section: Discussionmentioning
confidence: 93%
“…Any induced tCYP1A and/or tCYP3A enzyme activities can also be monitored using ethoxyresorufin-O-deethylas(EROD) or benzyloxy-4-trifluoromethylcoumarin-O-debenzyloxylase (BFCOD) activity assays, respectively. To estimate possible induced immunological responses and/or to explain differences among AHR modulations observed across species 46 , concentration-dependent effects on trout immunosuppression 25 , inflammation (downregulation of il6, crp , or upregulation of tgfb ) and/or T cell and macrophage activation 47 , may also be performed. Combining the information generated by in silico screening with future in vitro and in vivo experimentation, forms an integrative approach for unrevealling the bio-interactions and effects induced by nGs/nGOs and expanding our knowledge of these highly bio-interactive planar hydrophobic substances.…”
Section: Discussionmentioning
confidence: 99%